Autologous HIV-1 Clade-B Nef Peptides Elicit Increased Frequency, Breadth and Function of CD8+ T-Cells Compared to Consensus Peptides - Doroudchi, Mehrnoosh; Yegorov, Oleg; Baumgartner, Tom; Kernaleguen, Anne-Elen; Breton, Gaelle; Ndongala, Michel L.; Boulassel, Mohamed-Rachid; Routy, Jean-Pierre; Bernard, Nicole F.; Sékaly, Rafick-Pierre; Yassine-Diab, Bader (PLOS ONE, 2012)
Objective To determine the function and phenotype of CD8+ T-cells targeting consensus and autologous sequences of entire HIV-1 Nef protein. Methods Multiparameter flow cytometry-based analysis was used to evaluate the responses of two treatment naïve HIV-infected individuals, during primary and the chronic phases of infection. Results A greater breadth and magnitude of CD8 IFN-γ responses to autologous compared to clade-B consensus peptides was observed in both subjects. Cross recognition between autologous and consensus peptides decreased in both subjects during progression from primary to chronic infection. The frequencies of TEMRA and TEM CD8+ T-cells targeting autologous peptides were higher than those targeting consensus peptides and were more polyfunctional (IFN-γ+ Gr-B+ CD107a+). Conclusions Our data indicate superior sensitivity and specificity of autologous peptides. The functional and maturational aspects of “real” versus “cross-recognized” responses were also found to differ, highlighting the importance of a sequence-specific approach towards understanding HIV immune response.